Misdiagnosed groin pain in an elderly: Interdisciplinary network as a tool for cost-effective work-collaboration - Oskar Kwaczynski; Michael Klauser; Andrej M. Nowakowski; Debora Nowakowski; Massimo Ruffo; Christian B. Frank (SAGE Open Medical Case Reports, 2025)
This case report presents an uncommon case of misdiagnosed groin pain in an elderly individual, highlighting the complexities of diagnosing overlapping symptoms in aging populations. With a growing elderly population, healthcare professionals must navigate complex medical histories to provide accurate diagnoses and effective treatment. This case emphasizes the importance of interdisciplinary collaboration and cost-effective diagnostic tools in delivering patient-centered care. We describe the case of an 87-year-old male with a history of heart disease and coronary angiography, who developed groin pain. After excluding a hernia, the patient was referred to our department for further evaluation. Through a thorough medical history and diagnostic tools, including computed tomography (CT) scan and intraarticular infiltration, the underlying cause of the pain was accurately identified and treated. An 87-year-old male with heart disease and previous coronary angiography presented with groin pain. Initially evaluated elsewhere for a potential hernia, the patient believed a foreign body in his muscles was the source of his pain. However, a planning X-ray failed to reveal this. Upon referral, a thorough medical history was taken, and a CT scan was performed to locate the foreign body and assess its proximity to the femoral nerve. The CT scan confirmed a broken angiography catheter (3–40 mm) near the femoral nerve. Additionally, severe fourth-grade coxarthrosis was identified. Despite the patient’s belief that the foreign body caused his pain, we determined coxarthrosis was the main issue. An intraarticular infiltration provided pain relief, confirming the diagnosis, and a total hip arthroplasty with catheter removal was performed, resulting in complete pain relief. This case underscores the need for thorough evaluation and interdisciplinary collaboration in diagnosing complex conditions in elderly patients. Intraarticular infiltration remains a valuable diagnostic tool, even alongside advanced imaging, helping prevent unnecessary procedures and improving patient outcomes.